Efficacy of β‐lactam/β‐lactamase inhibitors to treat extended‐spectrum beta‐lactamase‐producing Enterobacterales bacteremia secondary to urinary tract infection in kidney transplant recipients (INCREMENT‐SOT Project). Issue 3 (4th January 2021) - Pierrotti, Ligia C.; Pérez‐Nadales, Elena; Fernández‐Ruiz, Mario; Gutiérrez‐Gutiérrez, Belén; Tan, Ban Hock; Carratalà, Jordi; Oriol, Isabel; Paul, Mical; Cohen‐Sinai, Noa; López‐Medrano, Francisco; San‐Juan, Rafael; Montejo, Miguel; et al.
Abstract: Background: Whether active therapy with β‐lactam/β‐lactamase inhibitors (BLBLI) is as affective as carbapenems for extended‐spectrum β‐lactamase‐producing Enterobacterales (ESBL‐E) bloodstream infection (BSI) secondary to urinary tract infection (UTI) in kidney transplant recipients (KTRs) remains unclear. Methods: We retrospectively evaluated 306 KTR admitted to 30 centers from January 2014 to October 2016. Therapeutic failure (lack of cure or clinical improvement and/or death from any cause) at days 7 and 30 from ESBL‐E BSI onset was the primary and secondary study outcomes, respectively. Results: Therapeutic failure at days 7 and 30 occurred in 8.2% (25/306) and 13.4% (41/306) of patients. Hospital‐acquired BSI (adjusted OR [aOR]: 4.10; 95% confidence interval [CI]: 1.50‐11.20) and Pitt score (aOR: 1.47; 95% CI: 1.21‐1.77) were independently associated with therapeutic failure at day 7. Age‐adjusted Charlson Index (aOR: 1.25; 95% CI: 1.05‐1.48), Pitt score (aOR: 1.72; 95% CI: 1.35‐2.17), and lymphocyte count ≤500 cells/μL at presentation (aOR: 3.16; 95% CI: 1.42‐7.06) predicted therapeutic failure at day 30. Carbapenem monotherapy (68.6%, primarily meropenem) was the most frequent active therapy, followed by BLBLI monotherapy (10.8%, mostly piperacillin‐tazobactam). Propensity score (PS)‐adjusted models revealed no significant impact of the choice of active therapy (carbapenem‐containing vs any other regimen, BLBLI‐ vs carbapenem‐based monotherapy) within the first 72 hours on any of the study outcomes. Conclusions: Our data suggest that active therapy based on BLBLI may be as effective as carbapenem‐containing regimens for ESBL‐E BSI secondary to UTI in the specific population of KTR. Potential residual confounding and unpowered sample size cannot be excluded (ClinicalTrials.gov identifier: NCT02852902).